2015
DOI: 10.1128/aem.00558-15
|View full text |Cite
|
Sign up to set email alerts
|

Feline Calicivirus, Murine Norovirus, Porcine Sapovirus, and Tulane Virus Survival on Postharvest Lettuce

Abstract: bHuman norovirus (HuNoV) is the leading cause of foodborne illnesses, with an increasing number of outbreaks associated with leafy greens. Because HuNoV cannot be routinely cultured, culturable feline calicivirus (FCV), murine norovirus (MNV), porcine sapovirus (SaV), and Tulane virus (TV) have been used as surrogates. These viruses are generated in different cell lines as infected cell lysates, which may differentially affect their stability. Our objective was to uniformly compare the survival of these viruse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 49 publications
1
21
0
1
Order By: Relevance
“…The survival of these viruses may differ between preharvest and postharvest environments, and survival on the leaf surfaces may differ from that within the leaf tissues. Multiple studies that have investigated the postharvest survival of HuNoV on fresh produce have shown that this virus or its calicivirus surrogates (MNV, SaV, and TV) can survive during the chilling storage period and well beyond the produce shelf life (17,30,(39)(40)(41)(42). For example, HuNoV inoculated onto cut lettuce pieces persisted at 4°C for the entire 14-day study period with only a 1-to 1.5-log-unit reduction in RNA titers (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The survival of these viruses may differ between preharvest and postharvest environments, and survival on the leaf surfaces may differ from that within the leaf tissues. Multiple studies that have investigated the postharvest survival of HuNoV on fresh produce have shown that this virus or its calicivirus surrogates (MNV, SaV, and TV) can survive during the chilling storage period and well beyond the produce shelf life (17,30,(39)(40)(41)(42). For example, HuNoV inoculated onto cut lettuce pieces persisted at 4°C for the entire 14-day study period with only a 1-to 1.5-log-unit reduction in RNA titers (39).…”
Section: Discussionmentioning
confidence: 99%
“…Following abiotic stress treatment, viral contamination of plant leaves was performed inside a biohazard hood. The suspension of feces containing HuNoV and the cell lysates of MNV, SaV, and TV were buffer exchanged to sterile water (to mimic contamination through irrigation water) using Amicon 100K Ultra-15 centrifugal devices (Millipore, Billerica, MA) that were centrifuged at 4,000 ϫ g for 0.5 h at 4°C as described previously (30). The titer of HuNoV RNA used in subsequent experiments was 6.3 Ϯ 0.1 log 10 genomic equivalent (GE)/ml.…”
Section: Preparation Of Virusesmentioning
confidence: 99%
“…Cell culture propagation of SaV and TV was performed as described previously (27) using the following cell lines: an LLC-porcine kidney cell line (LLC-PK1, ATCC CL-101) and an LLC-monkey kidney cell line (LLC-MK2, ATCC CCL-7), respectively. The HuNoV used in this study was HS194 strain (GenBank accession no.…”
Section: Preparation Of Virusesmentioning
confidence: 99%
“…One research team has used HuNoV in their studies and found significant internalization of the virus in lettuce and green onion under hydroponic growth conditions (24,25), while another team failed to detect any internalization of HuNoV in lettuce under hydroponic or soil growth conditions (26). This discrepancy, in addition to the fact that different surrogate viruses have been found to exhibit various degrees of similarity to HuNoV on leafy greens (21,27), necessitates a better assessment of the internalization dynamics of HuNoV in leafy greens, especially lettuce. Therefore, the objectives of this study were to (i) investigate whether lettuce and spinach can internalize HuNoV into the edible leaves, (ii) simultaneously assess the behavior of surrogate viruses TV and SaV in comparison with that of HuNoV, and (iii) determine whether HuNoV particles can be visualized inside lettuce and spinach tissues.…”
mentioning
confidence: 99%
“…The use of FCV as a surrogate of HuNoV should be avoided. MNV, taxonomically closely related to HuNoV, is known to be sensitive to ethanol Akasaka et al, 2016;Cromeans et al, 2014;Zonta et al, 2016 . Other surrogates including Tulane virus, porcine enteric calicivirus, porcine sapovirus, echovirus 12 and coliphage MS2 are also used Cromeans et al, 2014;Esseili et al, 2015;Kniel, 2014 . As a robust enterovirus, the use of CoV as a surrogate virus could be considered.…”
Section: Reportmentioning
confidence: 99%